Tetraband Small-Size Printed Strip MIMO Antenna for Mobile Handset Application - Qinghao Zeng; Yuan Yao; Shaohua Liu; Junsheng Yu; Peng Xie; Xiaodong Chen (International Journal of Antennas and Propagation)
A compact printed multiple-input multiple-output (MIMO) antenna for tetraband (GSM900/1800/1900/UMTS) mobile handset application is presented. The proposed MIMO antenna, which consists of two coupled-fed loop antennas with symmetrical configuration, was printed on a 120 * 60 * 0.8 mm3 Fr-4 substrate of relative permittivity of 4.4, loss tangent 0.02. Each element antenna requires only a small area of 22.5 * 25 mm2 on the circuit board. The edge-to-edge spacing between the two elements is only 0.03λ0 of 920 MHz. A slot and a dual-inverted-L-shaped ground branch were added in the ground plane to decrease the mature coupling between the antenna elements. The measured isolation of the proposed antenna is better than 15 dB among the four operating frequency bands. The simulated 3D radiation patterns at 900 MHz and 1900 MHz of both antenna elements show that two loop antennas in general cover complementary space regions with good diversity performance. Detailed antenna impedance matching performance comparisons were done to evaluate the benefit of using different decoupling technology. The envelop correlation coefficient is calculated to represent the diversity performance of the MIMO antenna.